Analysing the effectiveness of the rehabilitation and reintegration programmes at the Kgosi Mampuru II correctional facility - Van Dijk, Gerda (University of Pretoria, 2023)
Dissertation (MCom (Public Management and Policy))--University of Pretoria, 2022.